Inhibition of YAP/TAZ-TEAD activity induces cytotrophoblast differentiation into syncytiotrophoblast in human trophoblast - Mizutani, Tetsuya; Orisaka, Makoto; Miyazaki, Yumiko; Morichika, Ririko; Uesaka, Miki; Miyamoto, Kaoru; Yoshida, Yoshio (Molecular human reproduction, 2022)
During placentation, placental cytotrophoblast (CT) cells differentiate into syncytiotrophoblast (ST) cells and extravillous trophoblast (EVT) cells. In the placenta, the expression of various genes is regulated by the Hippo pathway through a transcription complex, Yes-associated protein (YAP)/transcriptional coactivator with PDZ-binding motif (TAZ)-TEA domain transcription factor (TEAD) (YAP/TAZ-TEAD) activity. YAP/TAZ-TEAD activity is controlled by multiple factors and signaling, such as cAMP signaling. cAMP signaling is believed to be involved in the regulation of trophoblast function but is not yet fully understood. Here we showed that YAP/TAZ-TEAD expressions and their activities were altered by cAMP stimulation in BeWo cells, a human choriocarcinoma cell line. The repression of YAP/TAZ-TEAD activity induced the expression of ST-specific genes without cAMP stimulation, and transduction of constitutively active YAP, i.e. YAP-5SA, resulted in the repression of 8Br-cAMP-induced expressions of ST-specific genes in a TEAD-dependent manner. We also investigated the role of YAP/TAZ-TEAD in maintaining CT cells and their differentiation into ST and EVT cells using human trophoblast stem (TS) cells. YAP/TAZ-TEAD activity was involved in maintaining the stemness of TS cells. Induction or repression of YAP/TAZ-TEAD activity resulted in marked changes in the expression of ST-specific genes. Using primary CT cells, which spontaneously differentiate into ST-like cells, the effects of YAP-5SA transduction were investigated, and the expression of ST-specific genes was found to be repressed. These results indicate that the inhibition of YAP/TAZ-TEAD activity, with or without cAMP stimulation, is essential for the differentiation of CT cells into ST cells.